2018
DOI: 10.1111/jvim.15219
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal aspergillosis: Outcome after topical treatment in dogs with cribriform plate lysis

Abstract: BackgroundCribriform lysis has been considered a contraindication for topical treatment of sinonasal aspergillosis (SNA) because of concerns about drug extravasation with resultant neurologic signs or death.Objective/HypothesisTo describe dogs with SNA and cribriform plate lysis treated with topical antifungal medications. Our hypothesis was that the conventional dogma that topical therapy should be avoided in these cases is incorrect.AnimalsNine client‐owned dogs with SNA and lysis of the cribriform plate, ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…However, the patient did not develop any neurological signs, and recent literature suggests that topical therapy is still appropriate in cases with cribriform plate lysis. 18 To the authors' knowledge, this is the first case report of S. apiospermum rhinosinusitis infection described in the United Kingdom.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, the patient did not develop any neurological signs, and recent literature suggests that topical therapy is still appropriate in cases with cribriform plate lysis. 18 To the authors' knowledge, this is the first case report of S. apiospermum rhinosinusitis infection described in the United Kingdom.…”
Section: Discussionmentioning
confidence: 82%
“…The lack of repeat imaging examination before topical intervention to restage the disease cannot exclude this scenario. However, the patient did not develop any neurological signs, and recent literature suggests that topical therapy is still appropriate in cases with cribriform plate lysis 18 …”
Section: Discussionmentioning
confidence: 82%
“…The time of infection and their micro-environments also differ. Knowledge of SNA is limited, and most studies have focused on diagnostics and treatment of dogs 5,30,[32][33][34] , on fungal resistance 27 and on the local immune response [6][7][8] . These studies suggested an induction of Th1 response during SNA.…”
Section: Discussionmentioning
confidence: 99%
“…Proper diagnosis of SNA requires a combination of computed tomography (CT), rhinoscopy, histopathology, cytology, fungal culturing, and serology 2 . Topical administration of azole drugs remains the most widely used and successful treatment for SNA in dogs although reports of its use are limited 2,3,5 . SNA has been associated with upregulation of Th1 cytokines like interleukin (IL)-8 and TNF-α [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…En caninos y felinos se presentan principalmente tres formas de aspergilosis: nasal, pulmonar e infecciones diseminadas. La aspergilosis nasal presenta frecuentemente sinusitis invasiva, ocasionada por las especies A. flavus, A. fumigatus y A. niger (Ballber et al, 2018;Belda et al, 2018). La de tipo pulmonar es de rara presentación y es causada por similares especies, además de A. versicolor (Maniam et al, 2017), mientras que la forma diseminada es una infección infrecuente, pero potencialmente fatal en perros, siendo las especies más aisladas A. terreus, A. deflectus y A. caninus (Kano et al, 2019;Yang et al, 2019), seguido en menor frecuencia por A. fumigatus (Brocal et al, 2019).…”
Section: Introductionunclassified